Pengaruh Komitmen Organisasi dan Kepuasan Kerja Terhadap Organizational Citizenship Behavior (OCB) Pada PT. Nusa Sarana Citra Bakti Baturaja - Dela Nogita Sari; Dahlia; Rosmala Dewi (Politeknik Negeri Sriwijaya, 2024)
This research aimed to determine the influence of organizational commitment and job satisfaction on organizational citizenship behavior (OCB) at PT. Nusa Sarana Citra Bakti Baturaja. The data collection technique in this research was through distributing questionnaires to a population of 40 people. The data analysis technique used was Multiple Linear Regression. Based on the results of the partial analysis, there was an influence of the Organizational Commitment variable on Organizational Citizenship Behavior (OCB) at PT. Nusa Sarana Citra Bakti Baturaja with a value of tcount 2.097>ttable 2.026, there was an influence of the variable Job Satisfaction on Organizational Citizenship Behavior (OCB) at PT. Nusa Sarana Citra Bakti Baturaja with a value of tcount 7.738>ttable 2.026, it was simultaneously found that there was an influence of Organizational Commitment and Job Satisfaction on Organizational Citizenship Behavior (OCB) at PT. Nusa Sarana Citra Bakti Baturaja with Fcount value of 31,290>Ftable 3.25. The coefficient of determination (R2) obtained was 0.628, this showed the contribution of the influence of Organizational Commitment and Job Satisfaction on Organizational Citizenship Behavior (OCB) at PT. Nusa Sarana Citra Bakti Baturaja amounted to 62.8% while the remaining 37.2% was influenced by other variables not mentioned in this research such as personality, employee morale and motivation.